THE ROLE OF TRANSFORMATIONAL LEADERSHIP IN FOSTERING BUSINESS MANAGEMENT SUSTAINABILITY: THE MEDIATING EFFECT OF SUSTAINABLE ORGANIZATIONAL CULTURE - Doan, Huy Hoang; Tran, Thi My Linh (AMNESIA (JURNAL MANAJEMEN SUMBER DAYA MANUSIA), 2025)
This study investigates the interplay between transformational leadership, sustainable organizational culture, and sustainable business management within high environmental impact industries, including energy, manufacturing, transportation, and construction. Employing a quantitative methodology, data were gathered from 287 managers and employees. The findings reveal that transformational leadership exerts a significant positive influence on sustainable organizational culture, which subsequently enhances sustainable business management. Moreover, sustainable organizational culture partially mediates the relationship between transformational leadership and sustainable business management, with an indirect effect. These results build on prior research by emphasizing the mediating role of organizational culture in industries facing substantial environmental challenges. The study enriches the leadership and sustainability literature by offering empirical insights into the mechanisms linking leadership to sustainable outcomes. Practically, it suggests that organizations should prioritize cultivating transformational leadership and a sustainability-focused culture to improve their economic, social, and environmental performance. The research highlights the need to align leadership strategies with cultural values to achieve enduring sustainability objectives.